Fuji-Xerox: repurposing to save money and reduce damage to the environment - Benn, Suzanne (Henry Stewart Talks, 2019)
This case study examines Fuji-Xerox’s eco-manufacturing centre. In centres like these, Fuji-Xerox is rebuilding and reprocessing used products for lease rather than sale. This has resulted in major R&D payoffs and significant savings across the business.